2014
DOI: 10.5539/jgg.v6n2p103
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Change, Impacts and Adaptation Strategies in Dutsin-Ma Local Government Area of Katsina State, Nigeria

Abstract: This paper aimed at examining local peoples’ perceptions on climate variability and change and strategies adopted in combating the impacts of the changes in Dutsin-Ma Local Government Area of Katsina State. A total of 242 questionnaires were administered to households’ heads in the eleven wards of the Local Government Area. Descriptive statistics such as frequency distribution, percentage and mean scores were used in data analysis. The result revealed that majority of the local people have a very good knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This is in line with the projection by ref [30] that, many countries in Sub-Saharan Africa would face water shortage fromnow on (not because of lower rainfall) but pollution and destruction of water systems, due to frequent floods. Decrease in crops yield is the next significantly perceived impact of the change among the respondents ( = 4.08); which agrees with the findings of [28] and [13], where they all found out that decrease in crops yield were significantly perceived as the impact of respondents. All other impacts were insignificantly perceived in the study area It shows that the model significantly fits the data, p>0.05 (Hosmer and Lemeshow test), with 67.5% predictive power (Nagelkerke test); while it classified 89.9% of the variance in climate change awareness among the respondents.…”
Section: Perceived Impacts Of Climate Change Among the Respondentssupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with the projection by ref [30] that, many countries in Sub-Saharan Africa would face water shortage fromnow on (not because of lower rainfall) but pollution and destruction of water systems, due to frequent floods. Decrease in crops yield is the next significantly perceived impact of the change among the respondents ( = 4.08); which agrees with the findings of [28] and [13], where they all found out that decrease in crops yield were significantly perceived as the impact of respondents. All other impacts were insignificantly perceived in the study area It shows that the model significantly fits the data, p>0.05 (Hosmer and Lemeshow test), with 67.5% predictive power (Nagelkerke test); while it classified 89.9% of the variance in climate change awareness among the respondents.…”
Section: Perceived Impacts Of Climate Change Among the Respondentssupporting
confidence: 89%
“…Page: 33 findings of [19] and [28], in which they all found a high level of climate change awareness among people of their respective study areas. However, a closer look at this result, revealed that the percentage of those who are not aware of the change were substantial (22%) as such, there is still long way to go with programmes and policies that will enhance the rural people's awareness of the phenomenon, for better advocacy and implementation of adaptation and mitigation programmes to the adverse change.…”
Section: Climate Change Awareness Among Thementioning
confidence: 96%
“…More so, in our experiment, it took shorter time specifically between 3 -5 days to get them completely dried to enhance pulverization to powder, compared to the sun-drying method that took up to 7 days over the same dry season period. But solar drying would be of greater advantage because of the generally high evapo-transpiration throughout the year [16] and high temperatures of up to 35˚C [17], as a result of the abundant solar radiation received in Dutsin-Ma town. It is free, while the oven-drying requires electricity which is mostly not available in the area.…”
Section: Resultsmentioning
confidence: 99%
“…The highest air temperature normally occurs in April/May and the lowest in December through February. The vegetation of the area is the Sudan Savanna type which combines the characteristics and species of both the Guinea and Sahel Savanna (Abaje et al, 2014).…”
Section: Experimental Sitementioning
confidence: 99%